Green Engineering Management Practices and Financial Performance in Clean Water Infrastructure Programs: Evidence from a Waqf-Based Initiative - Kurnia Adi Permana; Rully Andhika Karim (Greenation Research & Yayasan Global Resarch National, 2025)
Green engineering emphasizes the efficient use of resources, sustainable infrastructure delivery, and integrated management systems to support long-term environmental and financial performance. In clean water infrastructure programs, particularly those implemented through philanthropic and waqf-based initiatives, managerial effectiveness plays a critical role in ensuring project sustainability. This study investigates how knowledge management, organizational communication, and accountability shape the financial performance of a clean water infrastructure program at Institution X. Using a quantitative explanatory design, survey data from 84 personnel involved in project implementation were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that engineering management practices are implemented at a moderate level, while their impacts on financial performance are selective and mediated. Transparency shows a significant direct effect, whereas reporting and communication practices influence financial outcomes indirectly through knowledge sharing. Knowledge sharing emerges as the central mechanism linking governance and communication practices to efficient resource utilization and financial performance. The findings demonstrate that green infrastructure performance is not determined solely by technical design, but also by integrated engineering management practices that enhance coordination, knowledge utilization, and project sustainability.